joom | júm, n. (Oxford English Dictionary, 2023)
Objectives Chronic venous insufficiency (CVI) of the lower extremities negatively affects quality of life due to pain and cosmetic concerns. According to the muscle pump theory, lower extremity muscles contribute significantly to venous return; however, data regarding the relationship between muscle thickness, elasticity, and venous reflux are limited. This prospective study aimed to evaluate the association between lower extremity muscle reserve and elasticity with venous reflux and to investigate the usefulness of shear wave elastography (SWE) in monitoring treatment response. Methods Between August 2024 and January 2025, 25 consecutive patients with clinically diagnosed CVI were prospectively enrolled in this study. Clinical examination and Clinical-Etiological-Anatomical-Pathophysiological classification were performed in all individuals. Rectus femoris and gastrocnemius muscle thickness were measured by ultrasonography, and elasticity was assessed using SWE. Venous reflux parameters were evaluated with color Doppler ultrasonography. Following baseline assessment, all patients completed a structured physical therapy program. Clinical and radiological evaluations were repeated after treatment; then pre- and post-therapy findings were compared. Results Thirty-six extremities of 25 patients (11 bilateral) were included in this study. Post-treatment measurements demonstrated significant increases in rectus femoris and gastrocnemius muscle thickness and SWE values (p ≤ .03) and a significant decrease in femoral and popliteal vein reflux times (p = .01) compared to baseline values. Changes in rectus femoris SWE values showed a weak negative correlation with femoral vein reflux time (r = -0.36, p = .01). Increased gastrocnemius thickness was weakly and inversely correlated with popliteal vein reflux time (r = -0.35, p = .01). Conclusions Muscle thickness and elasticity assessed by ultrasonography and SWE are associated with reflux duration in CVI and may serve as useful adjunctive parameters for evaluating response to physical therapy. Larger studies are needed to confirm their clinical applicability.